(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study examines the gastro protective activity of ethanolic leaf extract ofCassia grandis Linn against aspirin induced peptic ulcers on swiss albino wistar rat. Oral aspirin treatment (300 mg/kg body weight) caused ulceration. Omeprazole (standard) was given to swiss albino wistar rats at a dose of 20 mg/kg body weight, and Cassia grandis Linn was given at doses of 200 and 400 mg/kg body weight once daily for 14 days prior to the development of ulcers. Gastric secretions parameters were assessed after the experiment